The Analysis of work environment and culture on service productivity with knowledge management mediation in Serang City Health Centers - Widaningsih, Dewi (2024)
The research aims to assess how much influence the work environment, work culture, and knowledge management have on service productivity at the Serang City Health Center. The difference with previous research by other researchers is the addition of other variables, namely the work environment and knowledge management. The quantitative research method used in this research is quantitative research. As many as 431 ASN at the Puskesmas in Serang City constitute the population in this study. The number of samples was determined based on the Slovin method; a total of 95 people participated. Smart PLS was used to analyze the questionnaire data. It can be seen that the work environment has a significant effect on knowledge management as well as work culture. Work culture has a large effect on service productivity, while the work environment has a large effect on knowledge management. There is a substantial relationship between knowledge management and service productivity. Knowledge management shows a significant relationship between the work environment and service productivity. The work environment has a significant impact on service productivity, as does knowledge management.